Preferensi Anggota terhadap Produk Pembiayaan Murabahah di BMT Al-Hijrah KAN Jabung Sumenep - Umi Qurrotul Aini; Taufiqur Rahman (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research is a research that discusses the preference of members for financing products at BMT Al-Hijrah Kan Jabung Sumenep, Murabahah buying and selling which is an eternal investment is also buying and selling financing in cash or credit according to Islamic principles. This study aims to elaborate on the factors that influence member preferences and the application of cheap products to the Standard Operating Procedures. This research method uses a qualitative approach to descriptive analysis with data collection techniques, namely observation and interviews. The results of the study confirm that the researcher obtained a description of research data and respondents' preference for murabahah financing products so that regulatory support, promotion and buying and selling rates are the most dominant factors or the main factors for member preferences in murabahah financing transactions at BMT Al-Hijrah.